Controversial Embodiment: Sport, Masculinity, Dis/Ability (Altre Modernità, 2015)
This essay is an attempt at investigating visible forms of complex, indeed controversial embodiment, with the specific intention of concentrating on the ways they interrogate delicate issues such as disability, masculinity and prosthetic sport performance. I intend to sound the shifting boundaries between dis-ability and super-ability as manifested in iconic figures such as Stelarc and, in other fields, Oscar Pistorius, whose unsteady position as privileged/disabled bladerunner seems to require – and indeed to gather – particularly intense scrutiny. I shall introduce a few contemporary discourses on corporeality and embodiment, which focus on the ‘troubling’ nature of auxiliary organs Freud refers to in the much contended paragraph I adopt as epigraph and guiding procedural light; I shall move from Butler and Giddens to Jean-Luc Nancy’s work on transplants and/as prostheses to include theoretical debates on disintegrating embodiment and disability studies, in order to proceed towards an analysis of the short-circuiting of allegedly secure practices of (masculine) embodiment in sport culture and theory.
Keywords: complex embodiment; disability; sport culture; performance; cyborg; Pistorius